EVALUATION OF THE PHYSICAL FITNESS AMONG THE STUDENTS OF SMP NEGERI UNGGUL IN THE DISTRICT OF ACEH BESAR - Marlina, Yeni; Rahayu, Tandiyo (The Journal of Educational Development, 2017)
This study is entitled "Evaluation of Physical Fitness among the Students of SMP Negeri Unggul in the District of Aceh Besar". In essence, physical fitness is a condition that reflects a person's ability to perform productive tasks without experiencing fatigue, which means that the stored energy is still available. This study aims to determine the level of physical fitness of the students of Superior Junior High Schools (SMP Negeri Unggul) in Aceh Besar District. The method in this research was descriptive research method. The population in this study was all of the superior Junior High Schools in the District of Aceh Besar. The sampling technique in this research was cluster sampling based on the location of the region, namely the highlands, lowlands and coastal areas. The samples in this study were the SMP Negeri 3 Ingin Jaya, SMP Negeri 1 Peukan Bada and SMP Negeri 1 Mesjid Raya. The number of samples in this study was 114 consisting of 44 females and 70 males. The data collection technique in this research was the field measurements using the Indonesia Physical Fitness Test (IPFT). The data in this study were analyzed using a percentage test. The result showed that the physical fitness of the students of SMP Negeri Ungul in Aceh Besar District was in the category of poor. It can be elaborated as follows. 0% in the very good category, 8% in the good category, 31% in the average category, 61% in the poor category, and 0% in the very poor category. The Junior High School learners in Aceh Besar District are suggested to be more enthusiastic in improving their physical fitness so that they can easily perform everyday activities. The physical education teachers are expected to provide teaching materials so that the motor movement towards the physical fitness of students increases.